Experimental and finite element analysis of bond-slip in reinforced concrete - Wolenski, A. R. V. (2015)
The modeling of reinforced concrete structures has taken advantage of the increasing progress on Computational Mechanics, in such way that complex phenomena, such as cracking and crushing, creep, reinforcement yielding, steel-concrete bond loss, can be modeled in a reasonable realistic way, using the proper set of numerical and computational resources. Among several options, the ones based on the Finite Element Method (FEM) allow complex analysis simulations of reinforced concrete structures, including the interaction of different nonlinear effects. This paper deals with the nonlinear finite element analysis of the bond-slip between reinforcing steel and concrete, taking into account an experimental study previously performed. The FEM analysis presented uses a combination of resources where the material behavior of concrete is described by the Microplane Constitutive Model, and an embedded reinforcement model is used to represent steel inside the concrete and take into account the effect of bond-slip. The FEM models were created using the INSANE (INteractive Structural ANalysis Environment) computational system, open source software that has a set of FEM tools for nonlinear analysis of reinforced concrete structures. The correlations between numerical-experimentals results and several parameters validate the proposed combination of resources and identifies the significance of various effects on the response.